The Behavioral Finance of MSMEs: Financial Inclusion and Financial Technology - Huda, Nurrizal; Risman, Asep (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2024)
This project is to gather empirical data on the topic to gain a better understanding of how financial technology, or Fintech, affects the financial behavior of micro, small, and medium-sized firms (MSMEs). 110 MSMEs spread over West Jakarta made up the sample in 2023. As part of the data gathering method, a random sample questionnaire with a 5-point Likert scale was created using the online tool Google Forms. The Structural Equation Modeling (SEM) model was applied to the data using Partial Least Squares (PLS) software. The results of the study show that financial inclusion and financial technology (Fintech) have a positive influence on MSMEs' financial behavior. Financial technology, or Fintech, may function as a mediator and positively influence MSMEs' financial behavior by promoting broader financial inclusion. This information will be useful to financial institutions, relevant governments, entrepreneurs, and business support organizations that aim to improve the financial behavior and practices of MSMEs. The significance of programs intended to promote good financial conduct, expand financial inclusion, and educate the public about the advantages of fintech in order to enable MSMEs to adopt more responsible financial practices.